في ظل نقص التقنيات الخاصة برصد غاز الرادون محليا ، دراسة مقارنة لتأكيد جدوى تطبيق المعادلات التجريبية لرصد وقياس جرعة هذا الغاز (Comprehensive Journal of Science, 2025)
The main objective of this research is to enhance the idea of relying on empirical equations in the field of radiation monitoring with more confidence of the results, as it exploited the convergence of results between a local study and a study conducted at the University of Mosul, Iraq, to monitor and measure natural occurring  radioactive materials (NORM) for samples of normal soil and fertilized soil, where the results of measuring the concentration of radon gas measured by the nuclear trace detector technique CR39 of the Iraqi study were convergent with the results of the local study that used empirical equations to measure the concentration of the same gas. This convergence of results was also for the radioactive series and hazard indicators, which pushes towards more confidence to the use of these equations with light of the significant shortage of these technologies locally. The main results of both studies were as follows: The Iraqi study readings for radon gas concentration for normal soil ranged between 1.56x103 and 2.26x103 Bq/m3, while in the local study they ranged between 6.7x103 and 8.1x103 Bq/m3, while the fertilized soil readings ranged between 3.02x103 and 4.42x103 Bq/m3, and the local study readings for fertilized soil ranged between 5.24x103 and 23.5x103 Bq/m3. The measured concentrations of naturally occurring radioactive materials (NORM) and the calculated risk indices, the concentrations of 40K, 232Th and 238U series for the Iraqi study for normal and fertilized soil ranged between 179 - 620 Bq/kg and 43 - 62 Bq/kg and 42 - 212 Bq/kg, respectively, while these concentrations in the local study ranged between 254 - 767 Bq/kg, 9 - 60 Bq/kg, and 7 - 110 Bq/kg, respectively. The annual effective dose risk index for the Iraqi study for normal and fertilized soil ranged between 0.64 - 1.22 mSv/y, while in the local study it ranged between 0.026 - 0.105 mSv/y. There is some noticeable discrepancy between the results of the two studies,  this is due to the nature of the soil and fertilizer used in both countries, rather than to a discrepancy between the two measurement methods.
Keywords: Radon gas - Empirical equations - CR39 - NORM - Fertilized soil